(untitled) (World Bulletin of Public Health, 2024)
This article provides an overview of the current issues of the interaction of filling materials with the microflora of the oral cavity. An increase in the efficiency of restoration of dental hard tissues and the prevention of secondary caries, periodontal diseases by optimizing the choice of filling materials is considered, and the mechanism of adhesion of oral microorganisms to filling materials will also be studied.